2023
DOI: 10.3389/fpubh.2023.1151225
|View full text |Cite
|
Sign up to set email alerts
|

Uptake patterns and predictors of colorectal cancer screening among adults resident in Spain: A population-based study from 2017 to 2020

Abstract: BackgroundAlthough population screening has improved the early diagnosis of colorectal cancer (CRC), most cases are diagnosed in symptomatic patients. This study aimed to estimate the prevalence and evolution over time of uptake patterns to fecal immunochemical test (FIT) as a screening test for CRC among individuals aged 50–69 in Spain, and to determine the predictive factors for uptake patterns to this type of screening based on sociodemographic, health, and lifestyle characteristics.MethodsA cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This strategic adjustment aligns with the flexibility endorsed by the Spanish Society of Epidemiology, which recognizes alternative groupings in social class categorization [35]. Moreover, our decision is reinforced by recent research within the same dataset, where the three-category approach was consistently utilized to characterize social class while investigating factors influencing screening test uptake for colorectal cancer [36]. Also, the consistency observed in contemporary epidemiological studies across diverse datasets in Spain further support our rationale [37,38].…”
supporting
confidence: 65%
“…This strategic adjustment aligns with the flexibility endorsed by the Spanish Society of Epidemiology, which recognizes alternative groupings in social class categorization [35]. Moreover, our decision is reinforced by recent research within the same dataset, where the three-category approach was consistently utilized to characterize social class while investigating factors influencing screening test uptake for colorectal cancer [36]. Also, the consistency observed in contemporary epidemiological studies across diverse datasets in Spain further support our rationale [37,38].…”
supporting
confidence: 65%
“…In addition to poor practice of good health habits, family history with CRC represented a core risk factor for developing the disease [32,34,36,44]. Similarly, Portero de la Cruz and Cebrino (2023) [67] found that socioeconomic status, level of education, social status and nationality were factors that intervened in the detection process. Also, a study conducted in a rural area demonstrated the needs for practitioners and the challenges that the population are faced with regarding the limitations of CRC screening [68].…”
Section: Discussionmentioning
confidence: 98%
“…These data are in agreement with a study conducted in Nebraska, where Gonzales et al (2023) [66] stated that CRC screening in conjunction with education are important points in the detection of the disease. Recently, a study in Spain concluded that the uptake of FIT (faecal immunochemical testing) between 2017 and 2020 increased, but the prevalence of FIT remains low compared to European guidelines [67].…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than what was found in Saudi Arabia [ 8 ]. On the other hand, higher screening practices were found in Spain and the USA, with 38% and 80%, respectively [ 9 , 10 ] The vast difference in the rate of screening practice could be due to differences in healthcare policies influencing guidelines between these countries. National policies and guidelines can influence screening practices in the sense that countries that have implemented systematic screening programs and have policies supporting routine screening tend to have higher screening rates for CRC.…”
Section: Discussionmentioning
confidence: 99%